Clonal expansion ofEscherichia coliST38 carrying a chromosomally integrated OXA‐48 carbapenemase gene. Issue 6 (June 2016) - Turton, Jane F.; Doumith, Michel; Hopkins, Katie L.; Perry, Claire; Meunier, Daniele; Woodford, Neil
Abstract : N/A: Many isolates of Escherichia coli carrying bla OXA‐48 referred to Public Health England's national reference laboratory during 2014 and 2015 shared similar pulsed‐field gel electrophoresis (PFGE) profiles, despite coming from patients in multiple different hospitals and regions. Whole genome sequencing on an Illumina platform revealed that these belonged to sequence type (ST) 38. The OXA‐48 gene is usually carried on a 62 kb IncL/M plasmid (pOXA48a), but those belonging to this ST appeared either to lack plasmid elements or to have only a partial complement. Two isolates, one belonging to a main cluster sharing identical PFGE profiles and the other having a distinct profile, were further sequenced on a minION. The long reads provided by the nanopore sequencing technology facilitated assembly of a much larger contig around the bla OXA‐48 region, showing that both isolates shared a similar arrangement, with a plasmid fragment containing bla OXA‐48 flanked by IS 1R elements integrated into the chromosome, although the length of the plasmid fragment and the insertion site differed between the two isolates. That belonging to the main cluster contained a 21.9 kb Tn 6237 insert, as previously described in E. coli EC‐15 from Lebanon, but in a different insertion site. PCR mapping indicated that a further 14/31 representatives of this cluster also contained this insert in the same insertion site, with most of the remainder differing only by having additional E. coli sequence on one side of the insertion. This sub‐cluster of ST38 was found from 25 different hospital laboratories, suggesting widespread distribution of a successful type.